2021
DOI: 10.3390/biom11060855
|View full text |Cite
|
Sign up to set email alerts
|

Can Antiviral Activity of Licorice Help Fight COVID-19 Infection?

Abstract: The phytotherapeutic properties of Glycyrrhiza glabra (licorice) extract are mainly attributed to glycyrrhizin (GR) and glycyrrhetinic acid (GA). Among their possible pharmacological actions, the ability to act against viruses belonging to different families, including SARS coronavirus, is particularly important. With the COVID-19 emergency and the urgent need for compounds to counteract the pandemic, the antiviral properties of GR and GA, as pure substances or as components of licorice extract, attracted atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 80 publications
(127 reference statements)
1
19
0
Order By: Relevance
“…Interestingly, glabridin suppressed SARS-CoV-2 infection at the full-time entry and post-entry treatments in viral protein levels. This behavior is reflected in a similar current result for the antiviral efficacy of glycyrrhizin, the primary active ingredient of licorice root [ 39 , 40 ]. However, glabridin also effectively inhibited SARS-CoV-2 at the entry treatment in our study.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, glabridin suppressed SARS-CoV-2 infection at the full-time entry and post-entry treatments in viral protein levels. This behavior is reflected in a similar current result for the antiviral efficacy of glycyrrhizin, the primary active ingredient of licorice root [ 39 , 40 ]. However, glabridin also effectively inhibited SARS-CoV-2 at the entry treatment in our study.…”
Section: Discussionsupporting
confidence: 66%
“…GR has a high affinity for S protein-mediated cell binding and thus blocks binding of recombinant S protein to host cells (Li et al 2021 ). In addition, several reviews and in silico docking studies have provided evidence for the potent effects of GR against SARS-CoV-2 replication and virus S protein binding to host cells (Gomaa and Abdel-Wadood 2021 ; Diomede et al 2021 ; Ahmad et al 2021 ; Zheng et al 2021 ; Zhang et al 2021a ; Huan et al 2021 ). Although there are no experimental studies to date investigating the effect of BA against SARS-CoV-2, several studies have shown the antiviral effect of BA against many other viruses (Badria et al 2003 ; Von Rhein et al 2016 ; Goswami et al 2018 ; Si et al 2018 ; Xiao et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…G. glabra and its active components have been shown promising results to combat SARS-CoV-2 infection and can be useful in treating patients with COVID-19 as on scientific evidences collected from some of the recently published reviews ( Bailly and Vergoten, 2020 ; Fatima et al, 2020 ; Huaccho-Rojas et al, 2020 ; Jezova et al, 2020 ; Murck, 2020 ; Srivastava et al, 2020 ; Adithya et al, 2021 ; Boozari and Hosseinzadeh, 2021 ; Jalali et al, 2021 ; Khan et al, 2021 ; Idrees et al, 2021 ; Brendler et al, 2021 ; Diomede et al, 2021 ; Liana and Phanumartwiwath, 2021 ; Malekmohammad et al, 2021 ; Merarchi et al, 2021 ). Several mechanisms have been identified and have been depicted in figure 4 .…”
Section: Potential Health Benefit Of G Glabra As Anti-inflammatory Antiviral and Immunomodulatory Agentsmentioning
confidence: 99%